Crystalline forms of camlipixant
Patent Information
- Application Number
- CN202580021091.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-15
- Filing Date
- 2025-03-13
- Publication Date
- 2026-10-16
Smart Images

Figure CN122935549A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a crystal form of camlipixant and its use in pharmaceutical compositions and therapies, particularly in the treatment of refractory chronic cough. Background Technology
[0002] P2X3 antagonists can be used to treat a variety of conditions, particularly refractory chronic cough. One specific P2X3 antagonist under development is called camlipixant.
[0003] A camlipixant crystal form suitable for development into a camlipixant for the treatment of refractory chronic cough is required. WO 2020 / 099923 describes certain camlipixant crystal forms, particularly those with A... Those characterized by a family type.
[0004] Other crystal forms of camlipixant that can be developed need to be provided. Summary of the Invention
[0005] According to a first aspect of the invention, a crystal form (V-type) of camlipixant is provided, characterized in that the X-ray powder diffraction (XRPD) pattern has peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ.
[0006] According to a second aspect of the invention, a crystalline form (T-type) of camlipixant is provided, characterized in that the X-ray powder diffraction (XRPD) pattern has peaks at 2θ angles of 5.5, 6.5, and 10.3 ± 0.2° 2θ.
[0007] According to a third aspect of the invention, a pharmaceutical composition is provided comprising a crystal form of camlipixant according to the first or second aspect.
[0008] According to a fourth aspect of the invention, a crystal form according to the first or second aspect is provided for treating cough, particularly refractory chronic cough.
[0009] According to a fifth aspect of the invention, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystal form according to the first or second aspect, or comprising administering a pharmaceutical composition according to the third aspect. Attached Figure Description
[0010] Figure 1 The X-ray powder diffraction (XRPD) pattern of the V-type crystal form of camlipixant is shown.
[0011] Figure 2 Differential scanning calorimetry (DSC) curves of the V-type crystal form of camlipixant are shown.
[0012] Figure 3 The thermogravimetric analysis (TGA) curves of the V-form of camlipixant are shown.
[0013] Figure 4 Gravimetric vapor adsorption (GVS) of the V-form of camlipixant is shown.
[0014] Figure 5 The X-ray (single crystal) structure of the V-type crystal form of camlipixant is shown.
[0015] Figure 6 The variable-temperature XRPD of the V-type crystal form of camlipixant is shown.
[0016] Figure 7 The variable humidity XRPD of the V-form of camlipixant is shown.
[0017] Figure 8 Solid-state NMR of the V-shaped crystal form of camlipixant is shown.
[0018] Figure 9 The X-ray powder diffraction (XRPD) pattern of the T-type crystal form of camlipixant is shown.
[0019] Figure 10 Differential scanning calorimetry (DSC) curves of the T-type crystal form of camlipixant are shown.
[0020] Figure 11 Thermogravimetric analysis (TGA) curves of the T-type crystal form of camlipixant are shown.
[0021] Figure 12 Gravimetric vapor adsorption (GVS) of the T-type crystal form of camlipixant is shown.
[0022] Figure 13 The variable humidity XRPD of the T-type crystal form of camlipixant is shown.
[0023] Figure 14 Solid-state NMR of the T-type crystal form of camlipixant is shown.
[0024] Figure 15 Solid-state NMR spectra of A-type, V-type, and T-type crystals were displayed. Detailed Implementation
[0025] definition
[0026] As used herein, the term “treatment” means to improve or stabilize a particular condition, to alleviate or eliminate the symptoms of the condition, to slow or eliminate the progression of the condition, and to prevent or delay the recurrence of the condition in a patient or subject who has previously had the condition.
[0027] “camlipixant” refers to methyl (2S)-2-({2-[2,6-difluoro-4-(methylcarbamoyl)phenyl]-7-methylimidazo[1,2-a]pyridin-3-yl}methyl)morpholine-4-carboxylate, i.e., compounds having the following structure or pharmaceutically acceptable salts thereof:
[0028] .
[0029] As used herein, the term "pharmaceutically acceptable salt" refers to a salt that retains the desired biological activity of the target compound and exhibits minimal undesirable toxicological effects. Such pharmaceutically acceptable salts can be prepared in situ during the final isolation and purification of the compound, or by reacting the purified compound, in its free acid or free base form, with a suitable base or acid, respectively.
[0030] The term "therapeutic effective amount" refers to the amount of the compound of the present invention that will elicit the desired biological response in the human body. This amount can vary depending on the compound, the disease and its severity, and the age and weight of the subject being treated.
[0031] Description of the implementation plan
[0032] In a first aspect of the invention, a crystal form (V-type) of camlipixant is provided, characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ.
[0033] In one embodiment, the crystal form (V-type) of camlipixant is characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, 13.3, 14.5, and 19.7 ± 0.2° 2θ.
[0034] In one embodiment, the crystal form (V-type) of camlipixant is characterized by a peak at the 2θ angle listed in Table 1a in the X-ray powder diffraction (XRPD) pattern. Peaks shown in bold are considered characteristic peaks.
[0035]
[0036]
[0037]
[0038]
[0039]
[0040] Table 1a
[0041] In one embodiment, the crystal form (V-type) of camlipixant is characterized by X-ray powder diffraction (XRPD) substantially being similar to... Figure 1 Consistent.
[0042] In one embodiment, the V-type crystal form of camlipixant is characterized by a single endotherm in the DSC curve with an onset temperature of approximately 164 °C.
[0043] In one embodiment, the V-form of camlipixant is characterized by a DSC curve that is substantially similar to... Figure 2 Consistent.
[0044] In one implementation, the V-type crystal form is characterized by a TGA curve that is substantially the same as... Figure 3 Consistent.
[0045] In one embodiment, the V-type crystal is characterized by solid-state NMR peaks at approximately 21.8, 52.1, 71.2, 129.2, 141.6, 165.6, and 167.1 ppm.
[0046] In one embodiment, the V-type crystal form is characterized by solid-state NMR containing at least one peak at about 21.8, 52.1, 71.2, 129.2, 141.6, 165.6 and 167.1 ppm.
[0047] In one embodiment, the V-type crystal form is characterized by solid-state NMR containing at least two peaks at about 21.8, 52.1, 71.2, 129.2, 141.6, 165.6 and 167.1 ppm.
[0048] In one embodiment, the V-type crystal form is characterized by solid-state NMR containing peaks at approximately 21.8, 52.1, 71.2, 129.2, 141.6, 165.6, and 167.1 ppm.
[0049] In one embodiment, the V-type crystal form is characterized by solid-state NMR peaks consistent with those shown in Table 1b. Peaks shown in bold are considered characteristic peaks.
[0050]
[0051] Table 1b
[0052] In one embodiment, the V-type crystal structure is characterized by solid-state NMR being substantially similar to... Figure 8 Consistent with the above.
[0053] In one embodiment, the V-type crystal is characterized by XRPD spectra having peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ, and DSC curves having a single endothermic peak with an onset temperature of approximately 164 °C.
[0054] In one embodiment, the V-type crystal is characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, 13.3, 14.5, and 19.7 ± 0.2° 2θ, and a DSC curve having a single endothermic peak with an onset temperature of approximately 164 °C.
[0055] In one embodiment, the V-shaped crystal form is characterized by X-ray powder diffraction (XRPD) being substantially similar to... Figure 1 Consistent, and the DSC curve is basically the same as Figure 2 Consistent.
[0056] In one embodiment, the V-type crystal is characterized by solid-state NMR peaks at approximately 21.8, 52.1, 71.2, 129.2, 141.6, 165.6, and 167.1 ppm, and the DSC curve has a single endothermic peak with an onset temperature of approximately 164 °C.
[0057] In one embodiment, the V-type crystal is characterized by solid-state NMR containing at least one peak at about 21.8, 52.1, 71.2, 129.2, 141.6, 165.6 and 167.1 ppm, and the DSC curve having a single endothermic peak with an onset temperature of about 164 °C.
[0058] In one embodiment, the V-type crystal is characterized by solid-state NMR containing peaks at approximately 21.8, 52.1, 71.2, 129.2, 141.6, 165.6, and 167.1 ppm, and the DSC curve having a single endothermic peak with an onset temperature of approximately 164 °C.
[0059] In one embodiment, the V-type crystal structure is characterized by solid-state NMR being substantially similar to... Figure 8 Consistent, and the DSC curve is basically the same as Figure 2 Consistent.
[0060] In one embodiment, the V-type crystal form is characterized by having at least two of the following properties:
[0061] (a) The XRPD map is basically the same as Figure 1 Consistent;
[0062] (b) The XRPD spectrum shows peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ;
[0063] (c) The DSC curve is basically the same as Figure 2 Consistent;
[0064] (d) The DSC curve has a single endothermic peak with an initial temperature of approximately 164 °C; or
[0065] (e) The TGA curve is basically the same as Figure 3 Consistent;
[0066] (f) The GVS curve is basically the same as Figure 4 Consistent;
[0067] (g) Solid-state NMR includes at least one peak at about 21.8, 52.1, 71.2, 129.2, 141.6, 165.6, and 167.1 ppm; or
[0068] (h) Solid-state NMR is basically the same as Figure 8 Consistent.
[0069] In one embodiment, the V-type crystal form is characterized by having at least two of the following properties:
[0070] (i) The XRPD map is basically the same as Figure 1 Consistent;
[0071] (j) The XRPD spectrum shows peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ;
[0072] (k) The DSC curve is basically the same as Figure 2 Consistent;
[0073] (l) The DSC curve has a single endothermic peak with an initial temperature of approximately 164°C; or
[0074] (m) The TGA curve is basically the same as Figure 3 Consistent.
[0075] It should be noted that all the XRPD peaks that are V-type characteristic peaks of camlipixant (i.e. 5.7, 7.4, 13.3, 14.5 and 19.7 ± 0.2° 2θ) are not present in the previously disclosed A-type XRPD of camlipixant.
[0076] It should be noted that the V-type characteristic peak at at least 7.4 ± 0.2° 2θ is not present in the previously disclosed A-type, K-type, N-type, O-type, or B-type XRPDs.
[0077] In one implementation, the V-shape of camlipixant is a variable hydrate.
[0078] In one embodiment, the V-type has a water content of about 0.9% at 20% RH and 25°C, or about 1.2% at 40% RH and 25°C, or about 1.4% at about 60% RH and 25°C, or about 1.5% at 90% RH and 25°C.
[0079] In one embodiment, the V-type has a water content of about 0.9% to about 1.5% at 20-90% RH and 25°C.
[0080] In one embodiment, the V-type has a water content of about 0.9% to about 1.4% at 20-60% RH and 25°C.
[0081] In one embodiment, the V-type has a water content of about 0.9% to about 1.2% at 20-40% RH and 25°C.
[0082] In a second aspect of the invention, a crystal form (T-type) of camlipixant is provided, characterized in that the X-ray powder diffraction (XRPD) pattern has peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ.
[0083] In one embodiment, the crystal form (T-type) of camlipixant is characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.5, 6.5, 7.9, 10.3, 13.0, 15.6, and 20.4 ± 0.2° 2θ.
[0084] In one embodiment, the crystalline form (T-type) of camlipixant is characterized by a peak at the 2θ angle listed in Table 2a in its X-ray powder diffraction (XRPD) pattern. Peaks shown in bold are considered characteristic peaks.
[0085]
[0086]
[0087] Table 2a
[0088] In one embodiment, the crystal form (T-type) of camlipixant is characterized by X-ray powder diffraction (XRPD) substantially being similar to... Figure 9 Consistent.
[0089] In one embodiment, the T-type crystal form of camlipixant is characterized by a single endothermic peak in the DSC curve with an onset temperature of approximately 103 °C.
[0090] In one embodiment, the T-type crystal form of camlipixant is characterized by a DSC curve that is substantially similar to... Figure 10 Consistent.
[0091] In one implementation, the T-type crystal form is characterized by its TGA curve being substantially the same as... Figure 11 Consistent.
[0092] according to Figure 11 The TGA curves shown indicate that the T-type decomposes into water upon heating. Therefore, the T-type decomposed material is considered to be a hydrate.
[0093] In one embodiment, the T-type crystal form is characterized by solid-state NMR peaks at approximately 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm.
[0094] In one embodiment, the T-type crystal form is characterized by solid-state NMR containing at least one peak at about 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm.
[0095] In one embodiment, the T-type crystal form is characterized by solid-state NMR containing at least two peaks at about 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm.
[0096] In one embodiment, the T-type crystal form is characterized by solid-state NMR containing peaks at approximately 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm.
[0097] In one embodiment, the T-type crystal form is characterized by solid-state NMR peaks consistent with those shown in Table 2b. Peaks shown in bold are considered characteristic peaks.
[0098]
[0099] Table 2b
[0100] In one implementation, the T-type crystal form is characterized by solid-state NMR being substantially similar to... Figure 14 Consistent with the above.
[0101] In one embodiment, the T-type crystal is characterized by XRPD spectra having peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ, and DSC curves having a single endothermic peak with an onset temperature of approximately 103 °C.
[0102] In one embodiment, the T-type crystal is characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.5, 6.5, 7.9, 10.3, 13.0, 15.6, and 20.4 ± 0.2° 2θ, and a DSC curve having a single endothermic peak with an onset temperature of approximately 103 °C.
[0103] In one embodiment, the T-type crystal form is characterized by X-ray powder diffraction (XRPD) being substantially similar to... Figure 9 Consistent, and the DSC curve is basically the same as Figure 10 Consistent.
[0104] In one embodiment, the T-type crystal form is characterized by solid-state NMR peaks at approximately 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm, and the DSC curve has a single endothermic peak with an onset temperature of approximately 103 °C.
[0105] In one embodiment, the T-type crystal form is characterized by solid-state NMR containing at least one peak at about 20.4, 64.1, 75.2, 132.2, 135.2, 162.1 and 163.6 ppm, and the DSC curve having a single endothermic peak with an onset temperature of about 103 °C.
[0106] In one embodiment, the T-type crystal form is characterized by solid-state NMR containing at least two peaks at about 20.4, 64.1, 75.2, 132.2, 135.2, 162.1 and 163.6 ppm, and the DSC curve having a single endothermic peak with an onset temperature of about 103 °C.
[0107] In one embodiment, the T-type crystal form is characterized by solid-state NMR containing peaks at approximately 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm, and the DSC curve having a single endothermic peak with an onset temperature of approximately 103 °C.
[0108] In one implementation, the T-type crystal form is characterized by solid-state NMR being substantially similar to... Figure 14 Consistent, and the DSC curve is basically the same as Figure 10 Consistent.
[0109] In one embodiment, the T-type crystal form is characterized by having at least two of the following properties:
[0110] (a) The XRPD map is basically the same as Figure 9 Consistent;
[0111] (b) The XRPD spectrum shows peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ;
[0112] (c) The DSC curve is basically the same as Figure 10 Consistent;
[0113] (d) The DSC curve has a single endothermic peak with an initial temperature of approximately 103 °C;
[0114] (e) The TGA curve is basically the same as Figure 11 Consistent;
[0115] (f) The TGA curve is basically the same as Figure 3 Consistent;
[0116] (g) The GVS curve is basically the same as Figure 12 Consistent;
[0117] (h) Solid-state NMR includes at least one peak at approximately 20.4, 64.1, 75.2, 132.2, 135.2, 162.1, and 163.6 ppm; or
[0118] (i) Solid-state NMR is basically the same as Figure 14 Consistent.
[0119] In one embodiment, the T-type crystal form is characterized by having at least two of the following properties:
[0120] (j) The XRPD map is basically the same as Figure 9 Consistent;
[0121] (k) The XRPD spectrum has peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ;
[0122] (l) The DSC curve is basically the same as Figure 10 Consistent;
[0123] (m) The DSC curve has a single endothermic peak with an initial temperature of approximately 103 °C; or
[0124] (n) The TGA curve is basically the same as Figure 11 Consistent.
[0125] It should be noted that all the XRPD peaks that are characteristic of the T-type of camlipixant (i.e., 5.5, 6.5, 7.9, 10.3, 13.0, 15.6 and 20.4 ± 0.2° 2θ) are not present in the previously disclosed XRPD of the A-type of camlipixant.
[0126] It should be noted that the T-type characteristic peak at at least 7.9 ± 0.2° 2θ is not present in the previously disclosed A-type, K-type, N-type, O-type, or B-type XRPDs.
[0127] When an XRPD pattern contains diffraction angles within ±0.2 degrees 2θ of a specified value, the XRPD pattern will be interpreted as containing diffraction angles "approximately" of this specified value (expressed in degrees 2θ). Furthermore, it is known and understood by those skilled in the art that the apparatus used to obtain X-ray powder diffraction (XRPD) patterns, humidity, temperature, powder crystal orientation, and other parameters involved may cause variations in the appearance, intensity, and position of lines / peaks in the diffraction pattern. The information provided herein is related to... Figure 1 A "substantially identical" X-ray powder diffraction pattern is considered by those skilled in the art to represent a pattern with the characteristics provided. Figure 1 The XRPD pattern is the XRPD pattern of a compound with the same crystal form as the compound. That is, the XRPD pattern can be compared with... Figure 1 The XRPD patterns may be the same as or slightly different from those described herein. Such XRPD patterns may not necessarily show every line / peak of the diffraction pattern described herein, and / or may show slight variations in the appearance, intensity, or positional shifts of said lines / peaks due to differences in the conditions involved in obtaining the data. Those skilled in the art can determine whether a sample of the crystalline compound has the same or different form as disclosed herein by comparing their XRPD patterns. For example, those skilled in the art can compare the XRPD patterns of different forms or groups of camlipixant samples with... Figure 1 By performing image overlay and utilizing expertise in the field, it is easy to determine whether the XRPD pattern of this sample is substantially consistent with the V-shaped XRPD pattern of camlipixant. If the XRPD pattern is substantially consistent with... Figure 1 If the sample form is consistent, it can be easily and accurately identified as the V-type of camlipixant. For the T-type corresponding to camlipixant... Figure 9 That's also true.
[0128] In one implementation, when measured using Cu Kα radiation at 1.54 Å, the V-type is characterized by an XRPD pattern with a peak at the 2θ angle. As described above, the V-type XRPD pattern is as follows: Figure 1 As shown in Table 1a above, the corresponding diffraction peaks and peak heights are also shown.
[0129] In one implementation, when measured using Cu Kα radiation at 1.54 Å, the T-type is characterized by an XRPD pattern with a peak at the 2θ angle. As described above, the T-type XRPD pattern is as follows: Figure 9 As shown in Table 2a above. The corresponding diffraction peaks and peak heights are shown in Table 2a above.
[0130] Treatment
[0131] In a fourth aspect of the invention, a crystal form of camlipixant according to the first or second aspect is provided for treating cough, particularly refractory chronic cough.
[0132] In particular, a crystal form (V-type) of camlipixant is provided for the treatment of cough, especially refractory chronic cough, characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ.
[0133] In one embodiment, a crystal form (V-type) of camlipixant is provided for the treatment of cough, particularly refractory chronic cough, characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, 13.3, 14.5, and 19.7 ± 0.2° 2θ.
[0134] In one embodiment, the crystal form (V-type) of camlipixant is characterized by a peak at the 2θ angle listed in Table 1a above in the X-ray powder diffraction (XRPD) pattern.
[0135] In one embodiment, a crystalline form of camlipixant is provided for treating cough, particularly refractory chronic cough, characterized by X-ray powder diffraction (XRPD) substantially similar to... Figure 1 Consistent.
[0136] Alternatively, a crystal form (T-type) of camlipixant is provided for the treatment of cough, particularly refractory chronic cough, characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ.
[0137] In one embodiment, a crystal form (T-type) of camlipixant is provided for the treatment of cough, particularly refractory chronic cough, characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.5, 6.5, 7.9, 10.3, 13.0, 15.6, and 20.4 ± 0.2° 2θ.
[0138] In one embodiment, the crystal form (T-type) of camlipixant is characterized by peaks at the 2θ angles listed in Table 2a above in the X-ray powder diffraction (XRPD) pattern.
[0139] In one embodiment, a crystalline form of camlipixant is provided for treating cough, particularly refractory chronic cough, characterized by X-ray powder diffraction (XRPD) substantially similar to... Figure 9 Consistent.
[0140] In a fifth aspect of the invention, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystal form according to the first or second aspect, or comprising administering a pharmaceutical composition according to the third aspect.
[0141] In particular, a method for treating cough, especially refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystalline form (V-form) of camlipixant, the crystalline form being characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ.
[0142] In one embodiment, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystalline form (V-type) of camlipixant, the crystalline form being characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.7, 7.4, 13.3, 14.5, and 19.7 ± 0.2° 2θ.
[0143] In one embodiment, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystalline form (V-form) of camlipixant, said crystalline form being characterized by X-ray powder diffraction (XRPD) substantially similar to... Figure 1 Consistent.
[0144] In one embodiment, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystalline form (T-type) of camlipixant, the crystalline form being characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ.
[0145] In one embodiment, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystalline form (T-type) of camlipixant, the crystalline form being characterized by X-ray powder diffraction (XRPD) patterns having peaks at 2θ angles of approximately 5.5, 6.5, 7.9, 10.3, 13.0, 15.6, and 20.4 ± 0.2° 2θ.
[0146] In one embodiment, a method for treating cough, particularly refractory chronic cough, is provided, comprising administering to the person a therapeutically effective amount of a crystalline form (T-type) of camlipixant, said crystalline form being characterized by X-ray powder diffraction (XRPD) substantially similar to... Figure 9 Consistent.
[0147] To avoid any doubt, refractory chronic cough can be defined as a cough that persists for ≥8 weeks despite adequate treatment of other cough-related conditions or an inability to determine the cause.
[0148] The following non-limiting embodiments illustrate the present invention.
[0149] Example
[0150] Compound 1 = Methyl (S)-2-((2-(2,6-difluoro-4-(methylcarbamoyl)phenyl)-7-methylimidazo[1,2-a]pyridin-3-yl)methyl)morpholine-4-carboxylate having the following structure
[0151]
[0152] V-shaped
[0153] preparation
[0154] Compound 1 (2 g) was slurried in water (100 mL) with magnetic stirring (300 rpm). The slurry was then heated to 80 °C and maintained for 7 days. The temperature was cooled to room temperature over 1 hour, the solid was separated by vacuum filtration, washed with water (50 mL), and then vacuum dried at 50 °C to separate the V-form of camlipixant.
[0155] The input material for compound 1 is in the A-type crystal form. The A-type of camlipixant can be prepared according to the disclosures in WO 2020 / 099923 and WO 2021 / 161109. For example, Example 2E in WO 2020 / 099923 relates to A... Preparation of type A. Alternatively, type A can be obtained according to Example 2A in WO 2020 / 099923, and then vacuum dried at 50°C.
[0156] Alternatively, the input substance used to generate the V-shape according to the above method can be amorphous compound 1.
[0157] V-type substitution preparation
[0158] Compound 1 was slurried in methanol (8.99 vol) and water (10 vol) and heated to 55 °C to dissolve. The mixture was then cooled to 50 °C, and water (0.5 vol) was added. The solution was seeded with V-type compound 1 (2 wt%), held for 1 hour, then more water (2.7 vol) was added and cooled to 40 °C. The final slurry was held for two days and the V-type was separated by vacuum filtration (39% w / w yield).
[0159] The input substance for Compound 1 can be prepared according to the procedure described in the previous section.
[0160] V-shaped seed materials can be prepared based on previous slurry experiments.
[0161] V-type substitution preparation
[0162] Amorphous compound 1 (20 mg) was suspended in 0.5 mL of anisole at 50 °C and stirred for 13 days. The solid was then separated and dried under vacuum to obtain V-type camlipixant.
[0163] Compound 1 can be prepared by any suitable method, such as the methods disclosed in WO 2014 / 117274, WO 2021 / 161109 or WO 2023 / 021328.
[0164] Characterization data
[0165] V-shaped XRPD is performed using the following method.
[0166] X-ray powder diffraction (XRPD) patterns were collected in a transmission configuration, where a Kapton membrane was used to hold the sample in place. Analytical parameters are shown in Table 3.
[0167]
[0168] Table 3
[0169] The XRPD spectrum of V-type camlipixant (compound 1) is as follows: Figure 1 As shown.
[0170] Differential scanning calorimetry (DSC) collects samples by heating a small amount of material in an aluminum disk to 250°C using N2 purge gas at a rate of 10°C / min. The resulting curve is shown below. Figure 2 As shown. Based on this, it can be concluded that the initial temperature of the V-shape is approximately 164°C.
[0171] Thermogravimetric analysis (TGA) was performed by heating a small sample in an aluminum dish to 250°C using N2 purge gas at a rate of 10°C / min. The resulting curve is shown below. Figure 3 As shown.
[0172] Gravimetric vapor adsorption (GVS) was collected using a DVS-Advantage instrument from Surface Measurements Systems (SMS) Ltd. Relative humidity was calibrated based on the deliquescence points of LiCl, MgCl2, and NaCl at 25°C.
[0173] Use the following parameters (Table 4):
[0174]
[0175] Table 4
[0176] The obtained curve is as follows Figure 4 As shown.
[0177] The V-shaped molecular structure of camlipixant was determined based on three-dimensional X-ray diffraction data, such as... Figure 5 As shown in Table 5, this study (details in Table 5) confirmed the V-type atomic connections of camlipixant, with the obtained bond lengths and bond angles perfectly matching the hypothesized structure. This structural determination also provided a clear assignment of the absolute configuration. The V-type of camlipixant contains a stereocenter and is an isomer with an S-configuration.
[0178]
[0179]
[0180] Table 5
[0181] Summary of crystal data, data collection and refinement for GSK5464714A V-type X-ray diffraction studies
[0182] Variable-temperature X-ray powder diffraction (VT-XRPD) patterns were collected in a reflective configuration. For example... Figure 6 As shown, when the material was heated to 150°C, no change was observed in the XRPD diffraction pattern, and the peak shift was <0.2° 2θ. No changes were observed at different temperatures.
[0183] The conditions for use are shown in Table 6.
[0184]
[0185] Table 6
[0186] Variable humidity X-ray powder diffraction (VH-XRPD) patterns were collected in a reflective configuration. (Example) Figure 7 As shown, when the material was exposed to an environment with a relative humidity as high as 90% RH, the XRPD diffraction pattern did not change, with a peak shift of <0.2° 2θ. No changes were observed at different humidity levels.
[0187] The conditions for use are shown in Table 7.
[0188] Based on the results and data collected from experiments with varying temperature and humidity, it can be seen that the V-type XRPD is essentially unaffected by temperature or humidity, thus providing an indication of the stability of the V-type under all measurement conditions.
[0189]
[0190] Table 7
[0191] Obtained using a Bruker Avance III NMR spectrometer. 13 solid-state NMR data, operations 1 The H frequency is 400.222 MHz. The spectrometer is equipped with a 4 mm dual-resonance magic-angle rotating probe, operating at a rotation frequency of 8 kHz. Spectra were obtained using cross-polarization. 1 A linear power ramp is used on the H channel to improve cross-polarization efficiency. Rotational sidebands are eliminated using a full-sideband suppression sequence. This is achieved using a SPINAL-64 sequence. 1 H decoupling. 13 The C chemical shift referenced 0 ppm (parts per million) for tetramethylsilane, with the carbonyl peak in 176.4 ppm of α-glycine used as a secondary reference.
[0192] As a variable hydrate, it is known that variations in the water content of the V-type will result in slight differences in peak shifts compared to the characteristic peak shifts of the V-type described in Table 8 below. The spectrum is as follows... Figure 8 As shown.
[0193]
[0194] Table 8
[0195] Biological solubility data
[0196] Using an electronic pipette (BRAND, HandyStep Touch Multidispenser), add 3 mL of 10 mM phosphate buffer (pH 6.8), 10 mM acetate buffer (pH 4.5), or 10 mM HCl buffer (pH 1.2) to each vial containing 3 mg of V-form API. Place the vials on a BioShake iQ set to 500 rpm and 37.5 °C. After 24 hours, aliquots of the sample are removed from each vial, filtered through a 0.45 μm PVDF filter, and solubility is determined by HPLC UV quantification. For the HCl sample at pH 1.2, visual evaluation is performed only.
[0197]
[0198] Table 9
[0199] Stability data
[0200] The stability of the V-type solids was evaluated at 40°C and 75% relative humidity (RH). No changes in solid form or purity were observed over a 6-month period.
[0201] The results are shown in Table 10.
[0202]
[0203] Table 10
[0204] Water activity data
[0205] Water activity experiments were conducted at 25°C using a methanol / water system to determine the critical water activity between the anhydrous and hydrated forms.
[0206] A 1:1 mass mixture of form A and form V was studied in a water activity assay. Approximately 5 mg of form A and form V were equilibrated with 1 ml of saturated camlipixant solutions of different water activities at 25 °C for 3 days. The suspensions were filtered and dried under ambient conditions for 10 minutes. The solid fraction was studied by XRPD.
[0207] The results are shown in Table 11.
[0208]
[0209] Table 11
[0210] The data in Table 11 show that the formation of form V is favored when the mixture of forms A and V is in solvent conditions with more water. Conversely, the formation of form A is favored when the mixture of forms A and V is in solvent conditions with less water. Therefore, it is assumed that form A is advantageous when camlipixant is formulated in a solid state (e.g., tablet form), while form V is advantageous when camlipixant is formulated in a suspension state (i.e., in the presence of water).
[0211] T-shaped
[0212] preparation
[0213] Water (2.1 mL) was added to compound 1 (323 mg), followed by methanol (4.9 mL), and the mixture was then slurried at room temperature for at least 16 hours. The solid was separated by vacuum filtration and then vacuum dried overnight at 50 °C to separate the T-type camlipixant.
[0214] The input substance for compound 1 is the A-type crystal form. The A-type camlipixant can be prepared according to the disclosures in WO 2020 / 099923 and WO2021 / 161109. For example, Example 2E in WO 2020 / 099923 involves A... Preparation of type A. Alternatively, type A can be obtained according to Example 2A in WO 2020 / 099923, and then vacuum dried at 50°C.
[0215] Alternatively, the input material used to generate the T-shape according to the above method can be amorphous compound 1.
[0216] T-type XRPD is performed using the following method.
[0217] X-ray powder diffraction (XRPD) patterns were collected in a transmission configuration, where a Kapton membrane was used to hold the sample in place. The analytical parameters are as follows:
[0218]
[0219] Table 12
[0220] The XRPD pattern of T-type camlipixant (compound 1) can be seen in... Figure 9 .
[0221] Differential scanning calorimetry (DSC) collects a small sample in an aluminum disk by heating it to 220°C with N2 purge gas at a rate of 10°C / min. The resulting curve is shown below. Figure 10 As shown. Based on this, it can be concluded that the initial temperature of the T-type is approximately 103°C.
[0222] Thermogravimetric analysis (TGA) was performed by heating a small sample in an aluminum dish to 300°C using N2 purge gas at a rate of 10°C / min. The resulting curve is shown below. Figure 11 As shown.
[0223] Gravimetric vapor adsorption (GVS) was collected using a DVS-Advantage instrument from Surface Measurements Systems (SMS) Ltd. Relative humidity was calibrated based on the deliquescence points of LiCl, MgCl2, and NaCl at 25°C.
[0224] The following parameters were used (Table 13):
[0225]
[0226] Table 13
[0227] The obtained curve is as follows Figure 12 As shown.
[0228] Variable humidity X-ray powder diffraction (VH-XRPD) patterns were collected in a reflective configuration. (Example) Figure 13 As shown, when the material was exposed to an environment with a relative humidity as high as 90% RH, the XRPD diffraction pattern did not change, with a peak shift of <0.2° 2θ. No changes were observed at different humidity levels.
[0229] Based on the variable humidity XRPD results, it can be seen that the XRPD of the T-type is basically unchanged with different humidity conditions, thus providing an indication of the stability of the T-type under all measurement conditions.
[0230] The conditions for use are shown in Table 14.
[0231]
[0232] Table 14
[0233] Solid-state NMR data were collected using the V-type method described above.
[0234] The peak shifts are listed in Table 15 below. Figure 14 The spectrum is provided.
[0235]
[0236] Biological solubility data
[0237] Using an electronic pipette (BRAND, HandyStep Touch Multidispenser), add 3 mL of 10 mM phosphate buffer (pH 6.8), 10 mM acetate buffer (pH 4.5), or 10 mM HCl buffer (pH 1.2) to each vial containing 3 mg of T-type API. Place the vials on a BioShakeiQ set to 500 rpm and 37.5 °C. After 24 hours, aliquots of the sample are removed from each vial, filtered through a 0.45 μm PVDF filter, and solubility is determined by HPLC-UV. For the HCl sample at pH 1.2, visual evaluation is performed only.
[0238]
[0239] Table 16
[0240] Stability data
[0241] The stability of the T-type solids was evaluated at 25°C and 60% relative humidity (RH). No changes in solid form or purity were observed over a 9-month period.
[0242] The results are shown in Table 17.
[0243]
[0244] Table 17
[0245] Comparison data
[0246] Characterization data
[0247] A comparison was made between A-type, V-type, and T-type solid-state NMR.
[0248] Obtained using a Bruker Avance III NMR spectrometer. 13 solid-state NMR data, operations 1 The H frequency is 400.222 MHz. The spectrometer is equipped with a 4 mm dual-resonance magic-angle rotating probe, operating at a rotation frequency of 8 kHz. Spectra were obtained using cross-polarization. 1 A linear power ramp is used on the H channel to improve cross-polarization efficiency. Rotational sidebands are eliminated using a full-sideband suppression sequence. This is achieved using a SPINAL-64 sequence. 1 H decoupling. 13 The C chemical shift referenced 0 ppm (parts per million) for tetramethylsilane, with the carbonyl peak in 176.4 ppm of α-glycine used as a secondary reference.
[0249] As a variable hydrate, it is known that variations in the water content of type A will result in slight differences in peak shift compared to the characteristic peak shifts of type A as described in Table 18.
[0250]
[0251]
[0252] Table 18
[0253] Comparison of solid-state NMR spectra Figure 15 As shown.
[0254] Biological related solubility
[0255] As described above, type A camlipixant can be prepared according to the disclosures in WO 2020 / 099923 and WO 2021 / 161109. The biorelevant solubility of type A was evaluated according to the procedures described above for types V and T, and the results are provided in Table 19 below.
[0256]
[0257] Table 19
[0258] By comparing the biorelevant solubility of forms A and V, it can be seen that form V has lower solubility than form A. Therefore, form V is expected to be more stable in the presence of water.
Claims
1. A V-shaped crystal form of camlipixant, characterized in that... The X-ray powder diffraction (XRPD) pattern shows peaks at 2θ angles of approximately 5.7, 7.4, and 13.3 ± 0.2° 2θ.
2. The crystal form according to claim 1, characterized in that... The XRPD spectrum has peaks at 2θ angles of approximately 5.7, 7.4, 13.3, 14.5, and 19.7 ± 0.2° 2θ.
3. The crystal form according to claim 1 or 2, characterized in that... The XRPD map is basically consistent with Figure 1.
4. The crystal form according to any one of claims 1 to 3, wherein the crystal form is characterized in that the DSC curve has a single endothermic peak with an onset temperature of about 164°C.
5. The crystal form according to any one of claims 1 to 4, wherein the crystal form is characterized in that the DSC curve is substantially consistent with FIG2.
6. The crystal form according to any one of claims 1 to 5, wherein the crystal form is characterized by having peaks in solid-state NMR at about 21.8, 52.1, 71.2, 129.2, 141.6, 165.6 and 167.1 ppm.
7. The crystal form according to any one of claims 1 to 6, wherein the crystal form is characterized in that the solid-state NMR is substantially consistent with FIG.
15.
8. A T-type crystal form of camlipixant, characterized in that... The X-ray powder diffraction (XRPD) pattern shows peaks at 2θ angles of approximately 5.5, 6.5, and 10.3 ± 0.2° 2θ.
9. The crystal form according to claim 8, characterized in that... The XRPD spectrum has peaks at 2θ angles of approximately 5.5, 6.5, 7.9, 10.3, 13.0, 15.6, and 20.4 ± 0.2° 2θ.
10. The crystal form according to claim 8 or 9, characterized in that... The XRPD map is basically consistent with Figure 9.
11. The crystal form according to any one of claims 8 to 10, wherein the crystal form is characterized in that the DSC curve has a single endothermic peak with an onset temperature of about 103°C.
12. The crystal form according to any one of claims 8 to 11, wherein the crystal form is characterized in that the DSC curve is substantially consistent with FIG10.
13. The crystal form according to any one of claims 8 to 12, wherein the crystal form is characterized by having peaks in solid-state NMR at about 20.4, 64.1, 75.2, 132.2, 135.2, 162.1 and 163.6 ppm.
14. The crystal form according to any one of claims 8 to 13, wherein the crystal form is characterized in that the solid-state NMR is substantially consistent with FIG.
15.
15. A pharmaceutical composition comprising the crystal form of any one of claims 1-14 and at least one inactive ingredient selected from pharmaceutically acceptable excipients, diluents or carriers.
16. The pharmaceutical composition of claim 15, wherein the composition is formulated for oral administration.
17. The crystal form according to any one of claims 1 to 14 or the pharmaceutical composition according to claim 15 or 16, for the treatment of cough.
18. The crystal form or pharmaceutical composition according to claim 17, wherein the cough is a chronic cough or an acute cough.
19. The crystal form or pharmaceutical composition according to claim 17 or 18, wherein the cough is a refractory chronic cough.
20. A method for treating a person with a cough, the method comprising administering to the person a therapeutically effective amount of the crystal form according to any one of claims 1 to 14 or the pharmaceutical composition according to claim 15 or 16.
21. The treatment method of claim 20, wherein the cough is a chronic cough or an acute cough.
22. The treatment method according to claim 20 or 21, wherein the cough is a refractory chronic cough.
Citation Information
Patent Citations
Imidazopyridine compounds and uses thereof
WO2014117274A1
Crystalline forms of a substituted imidazopyridine compound and use thereof as p2x3 modulator
WO2020099923A1
Preparation of a p2x3 antagonist
WO2021161109A1
Preparation of a p2x3 antagonist
WO2023021328A1